PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN ALOKASI DANA DESA DI DESA WALEWANGKO KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA - RORONG, ONICA MEIVA; RORONG, ARIE JUNUS; LONDA, VERY (Sam Ratulangi University, 2018)
This study aims to identify and describe community empowerment through the utilization of Village FundAllocation (ADD) in Walewangko Village, West Langowan Subdistrict, Minahasa District.The research method used in this research is qualitative method. The main instrument in this study is theresearchers themselves; while the data collection techniques used are Interview, Observation,Documentation.The results showed that community empowerment through the utilization of Village Fund Allocation canimprove the empowerment of the small or less capable communities. community empowerment activitiesthrough the utilization of Village Fund Allocation in the Village Walewangko still limited or still reach asmall part of societyKeywords: Empowerment, Allocation of Village Funds